LENGTH-WEIGHT AND LENGTH-LENGTH RELATIONSHIPS FOR 12 FISH SPECIES FROM AN ESTUARINE ECOSYSTEM FROM GULF OF CALIFORNIA, MEXICO - González-Acosta, Adrián F. (2021)
Length - weight (LW) and standard length - total length (LL) relationships were assessed for 12 fish species caught in the Mulege River estuary (middle Gulf of California), Mexico. Fish were sampled in November 2011 and January 2012, using cast nets and gill nets (mesh size 3 mm). Parameters of the LW and LL relationships were estimated using the log-linear and simple linear regressions. Values of b parameter ranged from 2.39 in Lile stolifera (Jordan & Gilbert, 1882) to 3.16 in Mugil curema Valenciennes, 1836. LL relationships were significantly correlated, ranging 0.851 to 0.999. This study reports for the first time, LL relationships for three species (Ctenogobius sagittula (Günther, 1861), Erotelis armiger (Jordan & Richardson, 1895), and L. nigrofasciata Castro-Aguirre, Ruiz-Campos & Balart, 2002). The information reported here will be useful to generate a baseline for regulation as well as for a sustainable fishery management in one of the two positive estuarine ecosystems known in the Gulf of California.